2022
DOI: 10.1097/dcr.0000000000002156
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Imaging Using Indocyanine Green for Laparoscopic Lateral Pelvic Lymph Node Dissection for Clinical Stage II/III Middle-Lower Rectal Cancer: A Propensity Score-Matched Cohort Study

Abstract: BACKGROUND:The examination of the efficacy of nearinfrared imaging using indocyanine green in laparoscopic lateral pelvic lymph node dissection remains insufficient. OBJECTIVE:The aim of this study was to examine whether near-infrared imaging contributed to an increase in the total number of harvested lateral pelvic lymph nodes in laparoscopic lateral pelvic lymph node dissection.DESIGN: This was a retrospective, multi-institutional study with propensity score matching. SETTINGS:We conducted this study within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…It can decrease incorrect operations at the wrong level and reduce unnecessary damage to vessels and nerves during the process. This is the basic principle to avoid accidental bleeding and damage during LPND ( 2 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It can decrease incorrect operations at the wrong level and reduce unnecessary damage to vessels and nerves during the process. This is the basic principle to avoid accidental bleeding and damage during LPND ( 2 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lateral pelvic lymph node metastasis is an important metastasis pathway of middle and low rectal cancer ( 1 , 2 ). Sugihara et al ( 32 ) found that the overall survival rate of patients with LPNM was significantly lower than that of patients with negative LPNM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations